The answer is (3 x 8) + 6
Answer:
5
Step-by-step explanation:
The 6th term of an arithmetic progression is 35 and the 13th term is 77. find the 1st term
We know we have an arithmetic sequence.
a_n = (n - 1)*d + a_1
given:
a_6 = 35 = (6-1)*d + a_1
a_13 = (13 -1)*d + a_1 = 77
find a_1
we have 35 = 5d + a_1
and 77 = 12d + a_1
2 equations in 2 unknowns.
We can solve this.
77 = 12d + a_1
35 = 5d + a_1
minus the 2 equations from each other.
77 - 35 = 12d - 5d + a_1 - a_1
42 = 7d
d = 6
Find a_1
35 = 5*6 + a_1
35 = 30 + a_1
a_1 = 35 -30 = 5
a_1 = 5
Answer:
D
Step-by-step explanation:
To shift down:
F(x)-b
To shift up:
F(x)+b
To shift right:
F(x-b)
To shift left:
F(x+b)